Salmonella Typhimurium Outbreak Associated with Veterinary Clinic - Cherry, Bryan (Centers for Disease Control and Prevention, 2004)
A Salmonella enterica serovar Typhimurium outbreak was associated with a veterinary clinic. Confirmed cases were in one cat, two veterinary technicians, four persons associated with clinic patients, and a nurse not linked to the clinic. This outbreak emphasizes the importance of strong public health ties to the animal health community.